Melodic engagement: unveiling interactions dynamics in deaf content on tiktok with @jennifernatalie_ - Setyaningsih, Santi; Utari, Prahastiwi; Satyawan, Ign Agung (Master of Communication Science Program, Universitas Diponegoro, 2025)
Social media has evolved into an inclusive communication tool, enabling individuals with disabilities to share various messages with the broader public. This study explores how the educational content shared by the TikTok account @jennifernatalie_ fosters audience engagement with deaf-related issues. Using a qualitative approach through content analysis, the research examines how five dimensions of Social Media Influencer (SMI) communication—namely information usefulness, dialogic interaction, affectivity, collectivity, and connectivity—are manifested in the content uploaded. The analysis was conducted on 189 selected videos from four educational-themed playlists. Findings indicate that despite verbal communication limitations, @jennifernatalie_ effectively utilizes social media features to communicate in a creative and inclusive manner, delivering messages that foster emotional connection and interactive engagement. Through her authentic expression as a deaf individual, she succeeds in activating audience participation via comments, likes, and two-way conversations. This study highlights how influencer communication characteristics play a pivotal role in shaping engagement, particularly in disability-related topics. The findings contribute to a deeper understanding of inclusive communication practices on social media and the role of disabled influencers in fostering digital social interaction.